Prokaryotic communities associated with marine hydrothermal systems of the Gulf of California - Aguila-Ramírez, Ruth Noemí; González-Acosta, Bárbara; Gutiérrez-Almada, Karla María; Borges-Souza, José Manuel; Cervantes-Gámez, Rocío Guadalupe; Quiróz-Guzmán, Eduardo (Frontiers in Microbiology, 2025)
IntroductionMarine hydrothermal systems (MHS) are considered extreme environments due to their unique physicochemical conditions, which are challenging for most organisms. This study investigates the microbial communities in three MHS sites in Baja California Sur, Mexico.MethodsSediment samples were collected in two seasons of the year: rainy and dry season. Bacterial DNA was extracted, the V3-V4 regions of the 16S rRNA gene were amplified.Results and discussionThe analysis of microbial community structure and composition revealed that species richness and diversity were higher at control sites (not influenced by hydrothermal conditions). Samples from the MHS showed temporal variation in richness, as measured by the Chao1 index. Alphaproteobacteria and Gammaproteobacteria were the dominant classes. No significant differences in community structure were found between the seasons or between the control and MHS sites. However, the analysis did reveal differences in community structure among the three hydrothermal locations: Burro, Santispac, and Agua Caliente. The presence of Gammaproteobacteria, Alphaproteobacteria, Deltaproteobacteria, and Betaproteobacteria highlights their key roles in primary production within shallow hydrothermal systems, these microbial communities demonstrate their capacity to colonize diverse substrates. This study enhances the microbiological understanding of hydrothermal environments in Baja California Sur, and molecular analysis of unculturable microbes could provide further insights into their physiology and ecological roles in shallow hydrothermal systems.